GLOBAL AGENDA FOR SOCIAL WORK AND SOCIAL DEVELOPMENT: A PATH TOWARD SUSTAINABLE SOCIAL WORK - Lombard, Antoinette (Social Work/Maatskaplike Werk, 2015)
<span style="font-family: ’Times New Roman’,’serif’; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">The Global Agenda for Social Work and Social Development (2012) reflects the commitment of social workers, educators and social development practitioners to the Post-2015 Development Agenda. The 2030 Agenda for Sustainable Development, effective from September 2015, provides a framework for positioning the Global Agenda to contribute towards a more just society. This paper explores how the four commitments of the Global Agenda link with the 17 Sustainable Development Goals. Implications and opportunities relating to the Global Agenda for social work practice and education are discussed, and guidelines are presented for more sustainable development outcomes for social work practice and education.